Komposit La1-xSrxCo1-yFeyO3-d (LSCF) sebagai bahan katod tahan lama bagi sel fuel oksida pejal bersuhu sederhana-rendah: ulasan kajian - Hamimah Abd.Rahman,; Andanastuti Muchtar,; Norhamidi Muhamad,; Huda Abdullah, (2010)
Solid oxide fuel cell (SOFC) is the most efficient fuel cell with the ability to directly convert chemical energy into electrical energy. Although there are numerous advantages offered by SOFCs, such as high energy conversion efficiency, low noise, less emission of pollutants and flexibility of hydrocarbon fuels, the processing cost and the performance improvement of SOFCs are hindered due to the higher operational temperatures. Therefore, the tendency to reduce the operational temperature of SOFC has brought about the development of research in materials and fabrication technology of fuel cells. Recently, among the many types of cathode materials that have been studied, lanthanum strontium cobalt ferrite, La1-xSrxCo1-yFeyO3-d (LSCF) has been discovered to offer the most potential for use as cathode material in intermediate to low temperature SOFCs. The use of LSCF composite cathode has significantly reduced the cathode polarisation resistance and expanded the triple phase boundary (TPB) area available for oxygen reduction. The overall performance of cathodes and fuel cells are also influenced by the method of powder preparation and fabrication of the composite cathodes. As such, the present article focuses on the LSCF composites for use as durable cathode material in SOFCs from the aspects of materials development, powder preparation and fabrication techniques